Pharmacokinetic Exposures Associated With Oral Administration of Sorafenib in Dogs With Spontaneous Tumors - Cawley, Jacob R.; Stewart, Samuel D.; Mochel, Jonathan Paul; Veluvolu, Sridhar; Khanna, Chand; Fenger, Joelle M. (Frontiers in Veterinary Science, 2022)
Sorafenib is a multi-kinase small molecule inhibitor that targets serine/threonine and tyrosine kinases including the RAF kinase family, VEGFR-2, and PDGFR. The aim of this study was to evaluate the systemic pharmacokinetics of a previously defined tolerable oral dose of sorafenib in tumor-bearing dogs. Six client-owned dogs with a cytologic or histologic diagnosis of cancer were enrolled in this open-label, tolerability study. Dogs were administered sorafenib at an intended dose of 3 mg/kg and serum samples were obtained for analysis of sorafenib serum concentrations at 0, 1, 2, 6, 12, 24, 48, 72, 96, and 168 hours post-drug administration. Median time to peak serum sorafenib concentration occurred at 4 hours (range 2 – 12 hours) resulting in an average serum concentration of 54.9 ± 33.5 ng/mL (118.2 ± 72.1 nM). Mean sorafenib levels declined by over 70% relative to peak serum concentrations by 24 hours in all dogs, suggesting the value of at least twice daily administration. Doses of 3 mg/kg were well tolerated and no patients in the study experienced adverse events that were attributable to sorafenib. Future trials in dogs with cancer are recommended at this dosing schedule to assess the effect of sorafenib administration on anti-tumor efficacy signals and relevant pharmacodynamic target modulation in vivo.